2018
DOI: 10.20533/ijmip.2042.4647.2018.0048
|View full text |Cite
|
Sign up to set email alerts
|

A Review of m-Government Maturity Models

Abstract: Mobile government is gaining significant attention worldwide. Mobile phone penetration offers government a number of several opportunities, including offering governments services to citizens through ambiguous devices. This phenomenon called m-Government is a strategy which implicates the use of all kinds of wireless and mobile technologies, applications and devices for improving service delivery to the parties involved in m-Government including citizens, businesses, employees and all government divisions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…According to the author: "even a committee meeting can be held either on a train with mobile devices" [12] (p. 73). The authors of [17], [22], [23], [13] argue, that coordination of data and branches, communication between different layers of government and internal processes become better due to MGov potential. Direct access to databases, protocols, registers [15] (that was challenging even in the time of the diffusion of one-stop-shops centres development) become available in the case of better delivering of the public services.…”
Section: Methodsmentioning
confidence: 99%
“…According to the author: "even a committee meeting can be held either on a train with mobile devices" [12] (p. 73). The authors of [17], [22], [23], [13] argue, that coordination of data and branches, communication between different layers of government and internal processes become better due to MGov potential. Direct access to databases, protocols, registers [15] (that was challenging even in the time of the diffusion of one-stop-shops centres development) become available in the case of better delivering of the public services.…”
Section: Methodsmentioning
confidence: 99%
“…This would require that the government design universal applications on the mobile phones of citizens that allow them to, for example, pay bills and enquire about account balances. A recent survey by Dlamini and Mpekoa 26 concluded that the m-government system improves the communication of a country with its citizens. However, there are looming questions on how m-government systems can be prioritised through ethically sound processes whilst building citizens' trust.…”
Section: Mobile Government In South Africamentioning
confidence: 99%
“…36 An additional dilemma linked to the previous one is that local municipalities are faced with the ambiguous data protection law. 26 It does not give the local municipalities the jurisdiction to allow the residents to sign documents online. This puts the local government at a compromising position to fully commit to the m-government initiative.…”
Section: Local Mobile Government Ethical Dilemmasmentioning
confidence: 99%
“…may impact administrators' decisions concerning the adoption of digital tools. However most authors [13,16,23,25] argue, that coordination of data and branches, communication between different layers of government and internal processes become better due to MGov potential. Direct access to databases, protocols, registers [15] (that was challenging even in the time of the diffusion of citizen services centres development) become available in the case of better delivering of the public services.…”
Section: Mobile Government For More Effective E-governmentmentioning
confidence: 99%